“Moving Object Tracking In Videos:A Survey” - Mr. Yash A. Jaiswal, Ms. Ahilya A. Par, Mr.Abhijeet A.Chincholkar, (International Journal of Scientific Research and Management (IJSRM), 2014)
In this paper we presents a new approach for object based method in Video tracking. In this approach it fill/restore the missing/occluded part of background as well as moving fore objects of a video taken by a both stationary and mobile camera. This method differs from previous methods on video processing which work on 3 dimensional data. This method slices the image sequences along with motion manifold of travelling object, so that it reduces the search area for 3 dimensional by making conversion in 2 dimensional. To advance the computational efficiency based on geometric video analysis system approaches to touch up real videos under perspective distortion for the common camera motions, such as panning of camera, tilting angle, and zooming ratio. Result demonstration on algorithm is that it performs comparably better on 3 dimensional based methods, and however it modifies the recent repairing techniques to background damaged videos with projective effects, as well as velocity changes. To improve the performance of an object-based video tracking scheme that can solve the spatial consistency problem as well as the temporal continuity problem simultaneously. It comprised in three steps virtual contour construction, Key-posture selection and mapping and Synthetic posture generation. It improve the accuracy and efficiency of an object-based video tracking to make an intelligent tracking system.